The policy for the social participation in conservation : case study (2005)
Colombia is one the world's richest countries in biological resources. To protect them, Colombian Law created the National Parks in 1959. Further regulations for their creation and administration were approved during the seventies. However, they did not include mechanisms to balance conservation interests with other economic and social development priorities. Presently, the ample majority of the National Parks overlap with the traditional territories of indigenous, black and campesino communities. This affects their economies and imposes restrictions on the traditional uses of natural resources. In 2002 the national government approved the Policy for the Social Participation in Conservation which seeks to promote the implementation of conservation strategies with the participation of local stakeholders. To illustrate the effects of this Policy, and following the analytical framework of the WDR 2003 , the processes of declaration of two national parks are compared: Corales del Rosario National Park, and Alto Fagua Indiwasi National Park. Finally, the document presents a series of lessons and recommendations.